2019
DOI: 10.1038/s41379-019-0221-0
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis reveals two major architectural subgroups of prostate cancer growth patterns

Abstract: The Gleason score is one of the most important parameters for therapeutic decision-making in prostate cancer patients. Gleason growth patterns are defined by their histological features on 4- to 5-µm cross sections, and little is known about their three-dimensional architecture. Our objective was to characterize the three-dimensional architecture of prostate cancer growth patterns. Intact tissue punches (n = 46) of representative Gleason growth patterns from radical prostatectomy specimens were fluorescently s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 36 publications
2
43
0
1
Order By: Relevance
“…Benign and malignant prostate lesions can show overlapping morphological features on H&E slides. However, we found that the 3D architecture of most benign epithelial lesions was entirely different . For instance, simple and partial atrophy might closely resemble PCa on H&E and immunohistochemical stained slides, showing partial loss of basal cells .…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Benign and malignant prostate lesions can show overlapping morphological features on H&E slides. However, we found that the 3D architecture of most benign epithelial lesions was entirely different . For instance, simple and partial atrophy might closely resemble PCa on H&E and immunohistochemical stained slides, showing partial loss of basal cells .…”
Section: Discussionmentioning
confidence: 79%
“…These formed a disorganised network composed of luminal cells only and had no basal cell layer (Figure C,D). For a complete and comprehensive description of the 3D architecture of prostate adenocarcinoma growth patterns, we refer to our previous study …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the same group has extended this solvent‐based approach. Using iDISCO protocols they characterized 3D architecture of both benign and pre‐cancerous prostate lesions and described two distinct growth patterns of prostate cancer in patients . Notably, no group has taken up the matter of TOC of penis which, assumingly, would be valuable for deciphering of blood vessels and innervations patterns, with possible application to improve understanding of, for example, severe cases of erectile dysfunction.…”
Section: Application Of Toc For Particular Peripheral Organsmentioning
confidence: 99%